EFFECT OF UPPERCOTT EXPOSURE ON THE LIVER OF FEMALE ALBINO WISTAR RAT (FUDMA JOURNAL OF SCIENCES, 2023)
Improving technology has led to more dependence on agricultural pesticides and herbicides in the fight against pests. These pesticides have been shown to have harmful effects on man and other species. In this study, the hepatic effect of exposure to cypermethrin and dimethoate mixture (uppercott) was investigated in female albino wistar rats. Thirty (30) female wistar albino rats were distributed into five (5) groups of six (6) animals each. Groups 1 and 2 served as the normal control and oil control respectively, groups 3, 4 and 5 received 2.5%, 5% and 7.5% LD50 of uppercott orally for 28 days. Results obtained revealed that uppercott exposure significantly (p0.05) compared to the control. Superoxide dismutase (SOD) activity was significantly (p
Keywords: Alanine Transaminase, Alkaline Phosphatase, Aspartate Transaminase, Superoxide dismutase, Hepatotoxicity, Uppercott Pesticide